2023
DOI: 10.1007/s11356-023-28901-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in miR-134-3p expression and zDHHC3-AMPARs axis in association with aluminum neurotoxicity

Abstract: Aluminum (Al) is a neurotoxic substance associated with cognitive dysfunction and neurodegenerative diseases, such as Alzheimer's disease, but the mechanisms for aluminum neurotoxicity remain to be identi ed. In this work, we try to investigate a novel potential biomarker of cognitive dysfunction following aluminum exposure and the mechanism involved. Recently, miR-134-3p was reported as a novel regulator of cognitive function. To address this, we investigate the expression level of miR-134-3p in plasma from 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It was also found that zDHHC3 is a target of miR-134-3p. miR-134-3p is involved in aluminum neurotoxicity by targeting the zDHHC3-AMPARs axis, which could serve as a potential biomarker or useful target ( Song et al, 2023 ).…”
Section: Role Of Zdhhcs In Neurobiologymentioning
confidence: 99%
“…It was also found that zDHHC3 is a target of miR-134-3p. miR-134-3p is involved in aluminum neurotoxicity by targeting the zDHHC3-AMPARs axis, which could serve as a potential biomarker or useful target ( Song et al, 2023 ).…”
Section: Role Of Zdhhcs In Neurobiologymentioning
confidence: 99%